2001
DOI: 10.3171/jns.2001.94.1.0055
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance spectroscopy of brain hemangiopericytomas: high myoinositol concentrations and discrimination from meningiomas

Abstract: In this study the authors show that hemangiopericytomas could be clearly distinguished from meningiomas because they have a larger peak at 3.56 ppm. Measurements of extracts of the tumors and comparison of spectra acquired with MRS at long- (135-msec) and short- (20-msec) echo times established that this was due to the much higher levels of myoinositol in the hemangiopericytomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
58
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 22 publications
(15 reference statements)
6
58
0
2
Order By: Relevance
“…9, a prospective case from IDI (obtained in September 2003) is positioned in the classifier overview well beyond the menigioma area, and relatively close to the only validated haemangiopericytoma present in the database. Its spectral pattern is characterized by a high myo-inositol peak: haemangiopericytomas show a high peak at 3.55 ppm at short TE (STEAM 20 ms) and this peak diminishes at long TE (PRESS 135 ms), whereas meningiomas do not show a high signal at 3.55 either at short or long TE (6). Histological analysis of the postsurgical biopsy confirmed that it was indeed a haemangiopericytoma.…”
Section: Exploiting the Capabilities Of The Dssmentioning
confidence: 72%
See 2 more Smart Citations
“…9, a prospective case from IDI (obtained in September 2003) is positioned in the classifier overview well beyond the menigioma area, and relatively close to the only validated haemangiopericytoma present in the database. Its spectral pattern is characterized by a high myo-inositol peak: haemangiopericytomas show a high peak at 3.55 ppm at short TE (STEAM 20 ms) and this peak diminishes at long TE (PRESS 135 ms), whereas meningiomas do not show a high signal at 3.55 either at short or long TE (6). Histological analysis of the postsurgical biopsy confirmed that it was indeed a haemangiopericytoma.…”
Section: Exploiting the Capabilities Of The Dssmentioning
confidence: 72%
“…Visual examination of the 10 representatives for this group revealed that this was due to most of them having one of the two profiles, either being similar to the grade II mean with high myo-inositol and little lipid, or else with low myo-inositol and high lipids which is more like the profile of high-grade astrocytomas. Visual inspection of the other smaller groups revealed that the schwannomas appeared to have a low creatine and high cholines similar to meningiomas (and unlike astrocytomas), but additionally a large peak centred at 3.55 ppm [which is most probably from myo-inositol since there is negligible signal at 3.55 ppm in long TE spectra (6)]. In four out of the five cases the 3.55 ppm peak was higher than the choline peak.…”
Section: Spectral Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, there are only two reports on MRS of hemangiopericytomas (22,23), with only a single report on intraventricular hemangiopericytoma (23). Barba et al (22) studied three extraventricular hemangiopericytomas at both high and short TE and suggested that high mI obtained in hemangiopericytomas could be used to differentiate them from meningiomas. Hattingen et al (23) showed elevated Cho and reduced amounts of NAA and Cr but no mI in their spectrum from a intraventricular hemangiopericytoma.…”
Section: Other Intraventricular Tumorsmentioning
confidence: 99%
“…Examples of major 1 H NMR spectral variations reported in tumours, with respect to normal cells and tissues, are a generally elevated intensity of cholinecontaining metabolites ('Cho-peak', 3.2 p.p.m. ), mainly due to increased levels of phosphocholine (PCho) in brain, breast, prostate and other tumours (Negendank et al, 1996;Podo, 1999;Aboagye and Bhujwalla, 1999); loss of N-acetylaspartate, a putative neuroaminoacid, in gliomas (Ross, 2000); increase of myo-inositol in some brain tumours (Barba et al, 2001); and decrease of citrate in prostate carcinoma (Kurhanewicz et al, 1995). Furthermore, several tumour cells and tissue specimens exhibit 1 H NMR signals attributed to either membrane or intracellular mobile lipid domains (ML), whose fatty chains are endowed with a high degree of mobility, not compatible with the anisotropic packing in the lamellar phase (Mountford et al, 1993;Callies et al, 1993).…”
mentioning
confidence: 99%